FAKTOR – FAKTOR YANG MEMPENGARUHI KUALITAS AUDIT PADA KAP DI JAKARTA PADA PERIODE 2020 - Michael Jovanca Ega; Hendang Tanusdjaja (Fakultas Ekonomi Universitas Tarumanagara, 2022)
This research aims to examine the effect of auditor independence, auditor competence, audit fee, and audit tenure on audit quality. Primary data is the data used in this study. 94 questionnaires were distributed and 94 questionnaires were sent with the help of Google forms. The questionnaires returned and were used were 91 questionnaires. Data processing was performed using the logistic regression analysis method using SPSS version 25. The results obtained from this study indicate that auditor independence and auditor competence have a positive significant influence on audit quality. Meanwhile, audit fee and audit tenure didn’t have a significant influence on audit quality